Evaluation of physico-chemical and organoleptic characteristics of sweetened stirred plum (Prunes domestica) yoghurt during storage - Arora, Shalini; Chaudhary, Gaurav; Yadav, Upasana; Singh, Tarun Pal; Bathla, Shikha (Indian Journal of Dairy Science, 2021)
The objective of the present study was to develop sweetened stirred fruit yoghurt incorporated with plum fruit pulp. The pulp was added @ 10, 15 and 20% and the formulated sweetened fruit yoghurt was studied for various physico-chemical (pH, acidity, syneresis, and tyrosine value) and organoleptic characteristics during storage. Plain (natural) and plum yoghurt were observed significantly different and the results showed a significant (p<0.05) decrease in pH and increased acidity, syneresis, and tyrosine value among various treatments and during storage. The addition of plum fruit in natural yoghurt modified the sensorial characteristics of the formulated product. Fruit yoghurt prepared by the addition of plum at 10% level was most acceptable with significantly improved sensory characteristics and shelf life of 12 days during refrigerated storage.